2022
DOI: 10.1080/15502783.2022.2099757
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrocapsiate does not increase energy expenditure nor fat oxidation during aerobic exercise in men with overweight/obesity: a randomized, triple-blinded, placebo-controlled, crossover trial

Abstract: Background Prior evidence suggests that capsinoids ingestion may increase resting energy expenditure (EE) and fat oxidation (FATox), yet whether they can modulate those parameters during exercise conditions remains poorly understood. We hypothesized that dihydrocapsiate (DHC) ingestion would increase EE and specifically FATox during an acute bout of aerobic exercise at FATmax intensity (the intensity that elicits maximal fat oxidation during exercise [MFO]) in men with overweight/obesity. Since FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Contrary to our expectations, the results revealed that acute ingestion of dihydrocapsiate did not improve neuromuscular performance. These findings are in line with previous studies reporting that acute ingestion of capsinoids does not improve exercise performance during endurance ( Josse et al, 2010 ; Osuna‐Prieto et al, 2022 ; von Ah Morano et al, 2021 ). Potential explanations for these results may be (i) that the limited bioavailability of capsinoids in humans would not be enough to activate TRPV1 ( Bernard et al, 2008 ), and/or (ii) that the doses employed would not be too low to elicit any significant effects on neuromuscular performance.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to our expectations, the results revealed that acute ingestion of dihydrocapsiate did not improve neuromuscular performance. These findings are in line with previous studies reporting that acute ingestion of capsinoids does not improve exercise performance during endurance ( Josse et al, 2010 ; Osuna‐Prieto et al, 2022 ; von Ah Morano et al, 2021 ). Potential explanations for these results may be (i) that the limited bioavailability of capsinoids in humans would not be enough to activate TRPV1 ( Bernard et al, 2008 ), and/or (ii) that the doses employed would not be too low to elicit any significant effects on neuromuscular performance.…”
Section: Discussionsupporting
confidence: 92%
“…This fact is essential due to different factors such as the exercise intensity, metabolic cart use, or the ergometer employed, influence the metabolic responses during exercise ( Amaro-Gahete et al, 2018 ; Amaro-Gahete et al, 2019 ). Concerning the type of supplement used, previous studies revealed that capsinoids supplementation does not modulate the metabolic responses during aerobic exercise ( Osuna-Prieto et al, 2022 ; Rossi et al, 2022 ). Although a MFO protocol was used by Osuna-Prieto et al (2022) , previous research has reported that capsinoids are hydrolyzed in the gastrointestinal tract, and their metabolites are excreted rapidly after their ingestion ( Bernard et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was performed using the G* POWER software (Heinrich-Heine-Universität Düsseldorf, Germany) with an alpha of 0.05, an effect size of 0.4 and a statistical power of 0.80. Based on previous studies ( Josse et al, 2010 ; Osuna-Prieto et al, 2022 ), 12 participants were required to establish statistical differences between conditions. To ensure the detection of differences 17 physically active males were enrolled in the study ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations